Unusual posteromedial tubercle fracture extending to the talar dome. Issue 12 (10th September 2020) - Pappa, Eleni; Michalos, Michael; Zisis, Konstantinos; Koundis, George; Kokoroghiannis, Constantine; Evangelopoulos, Dimitrios
Abstract: The present case is unique in that the fracture of the posteromedial talar tubercule involved the tibiotalar rather than the subtalar joint as described in existing reports, which underlines the need for acute management by the Orthopaedic Surgeon Abstract : The present case is unique in that the fracture of the posteromedial talar tubercule involved the tibiotalar rather than the subtalar joint as described in existing reports, which underlines the need for acute management by the Orthopaedic Surgeon.